INTERRELATION BETWEEN FREE BAGGAGE ALLOWANCE AND TICKET PRICE IN AIR TRANSPORTATION - Ivannikova, V.; Manziuk, T.; Tabakar, T. (Science-based technologies, 2013)
In this article the notion of free baggage allowance and ticket price in air transportation are being studied. The problem is being considered in terms of active ways of decreasing maximum weight per each free checked baggage which also should be reasonable enough to produce a lower price of air ticket. Thus, the public interest in air transportation will increase. The investigation of the problem provided a clear view of need in reduction of free baggage allowance level. The research should also provide airlines’ stakeholders and governmental entities with an understanding of the potential of aviation taxes and fares as an innovative form of climate finance. The main goal of this research is to show the distinctions in ticket prices of low-cost carriers with different free baggage allowances. The intention of the case study was to undertake researches in the field of tariff formation in air passenger transportation with regard to the maximum permission on checked luggage. Also the article highlights such a problem in Ukrainian aviation market as lack of competitiveness.